Investigating the use of nudging to dissuade online banking fraud - Mutyavariri, Takudzwa Stanley (Rhodes University, Faculty of Commerce, Department of Information Systems)
Online banking is a service offered by most modern banks to provide their clients with a convenient means to access their bank accounts remotely. However, such convenience comes at a cost and has the potential to expose clients to online banking fraud. To mitigate such forms of fraud, banks make extensive use of traditional cybersecurity measures such as firewalls, intrusion detection systems, as well as personal identification numbers (PINs) and passwords. However, despite the use of such traditional cybersecurity measures, online banking fraud still occurs. In particular, traditional cybersecurity measures have difficulties detecting the unauthorised use of a customer's online banking credentials. For this reason, this study's main objective was to investigate the effectiveness of nudges when used to dissuade the unauthorised use of clients' online banking credentials. The study also had two secondary objectives: firstly, to identify where the deployment of nudges would be most effective; and secondly, to identify the rationalisations an individual may use to justify committing online banking fraud. Although previous research has sought to understand the use of nudges in various online contexts, none have done so within the context of online banking. Using a recontextualised version of the COM-B (capability, opportunity, motivation "“ behaviour) model of behaviour change, nudges were deployed in three versions of a fictitious online banking website. Following this, 15 semi-structured interviews were conducted with online banking users from the United States of America to understand how a third party may behave and rationalise their choices when they have unauthorised access to a customer's online banking credentials. The transcripts of these interviews were analysed using thematic analysis. The findings revealed that the most dissuasive nudges focused on encouraging individuals to empathise with the account holder. Nudges that increased the perception of an online banking website's security were also particularly dissuasive. The findings also indicated that the most effective place to deploy these nudges was after a user had logged in. Several rationalisations that enabled individuals to commit online baking fraud were found. The three most common were crime of opportunity, down on their luck, and sunk cost fallacy and curiosity. Together, the findings provide evidence to suggest that, if used effectively, nudges could prove useful as a means of dissuading online banking fraud, and even more so when combined with traditional cybersecurity measures.
Keywords: Electronic commerce -- Security measures; Bank fraud; Computer security; Behavioral cybersecurity; Decision making -- Data processing